ANALISIS HUBUNGAN SISTEM BANGUNAN DENGAN KINERJA TOTAL DAN INTEGRASI BANGUNAN PADA BERBAGAI GEDUNG BERTINGKAT DI SURABAYA - Herry Pintardi Chandra (Institute of Research and Community Outreach - Petra Christian University, 2001)
Factors in building system design have target in achieving maximum performance when they have proper correlation with total performance and building integrity. The purpose of this research is to find out the influence of building system: structural, envelope, mechanical and interior, to the performance and building integrity: spatial, thermal, indoor air quality, acoustical, and performance visual and building integrity. The analysis shows that: Structural system has dominant influence to the spatial performance, indoor air quality and building integrity (mean 4,75), envelope system has dominant influence to the thermal performance (mean 4,75), mechanical system has dominant influence to the visual performance (mean 5,00), interior system has dominant influence to the spatial performance (mean 4,75), In conclusion, there are differences in which building systems affect the total performance and building integrity. Abstract in Bahasa Indonesia : Faktor-faktor dalam desain sistem bangunan mempunyai sasaran dalam mencapai kinerja maksimum bila memiliki hubungan yang sesuai dengan kinerja total dan integrasi bangunan. Penelitian ini bertujuan untuk mengetahui sejauhmana faktor-faktor dalam sistem bangunan: structural, envelope, mechanical dan interior berpengaruh terhadap kinerja dan integrasi bangunan: spatial, thermal, indoor air quality, acoustical dan visual performance serta building integrity. Dari hasil analisis data, didapat: Structural system memiliki pengaruh yang dominan terhadap spatial performance, indoor air quality dan building integrity (mean 4,75), envelope system memiliki pengaruh yang dominan terhadap thermal performance (mean 4,75), mechanical system memiliki pengaruh yang dominan terhadap visual performance (mean 5,00), interior system memiliki pengaruh yang dominan terhadap spatial performance (mean 4,75). Disimpulkan bahwa terdapat perbedaan pengaruh desain sistem terhadap kinerja total dan integrasi bangunan.